Merdeka Belajar: Solution for Developing Creativity and Independence in Early Childhood in the Era of the Industrial Revolution 4.0 - Erni Munastiwi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Entering the era of the industrial revolution 4.0, the world has experienced many changes, especially the world of education. The data shows that creativity and independence are in the spotlight in the era of the industrial revolution 4.0, with high creativity and independence, children are able to compete and be able to answer national challenges. This research was conducted in order to analyze the independent learning correlation which is the solution of Developing Creativity and Independence of Early Childhood in the Industrial Revolution Era 4.0. The type of research used is quantitative research which is research based on the philosophy of positivism. The population in this study is educational institutions in one area, while the sample of this study is 3 schools. Samples were taken in Kindergarten B class and 10 children were taken from each school. Data collection in this study is use checklist questionnaire. Researchers tested the validity of the data using the validity test and reliability test. The result found Pearson correlation value between Pearson Creativity and Independence is 0.684 which is classified as having a strong relationship and the Sig value. (2-tailed) of 0.000 is smaller than 0.05. Based on these results, it can be seen that there is a significant relationship between independent learning and creativity with children's independence, with good creativity and independence. Children have readiness to face the challenges of an increasingly developing technological era.